Eine mikrosoziologisch inspirierte empirische Annäherung an die positive Generalprävention: Panelanalysen aus Deutschland mit gemischten Befunden - Hirtenlehner, Helmut; Reinecke, Jost; Stemmler, Mark (Monatsschrift für Kriminologie und Strafrechtsreform, 2023)
Positive general prevention assumes that observable criminal punishment stabilizes the audience s moral values, which in turn fosters compliance with the law. This harmonizes with a chain of relationships on the individual level according to which people s sanction risk estimates influence their acceptance of legal rules, with the latter facilitating adherence to the law. Despite the significance of the idea of positive general prevention in the jurisprudential discourse, only scant empirical research is dedicated to the issue. Hence, the impact chain outlined above is tested here with panel data from adolescents living in Dortmund or Nuremberg. Lagged path analyses corroborate the hypothesized effect sequence for shoplifting (with weak relationships in the expected direction), but not for physical assault. These findings are interpreted as partially supportive of the notion of positive general prevention. The hypothesis that delinquent friends transmit information about the widespread impunity of criminal behavior and thus attenuate an individual s commitment to the rules of law accords also well with the idea of positive general prevention. Lagged analyses confirm for physical assault, but not for shoplift-ing, that association with delinquent peers erodes young people s personal acceptance of legal norms.
CRIS-Team Scopus Importer:2023-04-14
Keywords: norm acceptance; panel analysis; peer delinquency; positive general prevention